029 Management and outcomes of patients following out-of-hospital cardiac arrest. (16th May 2012) - Khan, S; Saidmeerasah, A; Hunjan, R; Wright, R; Swanson, N; Sutton, A; Muir, D; Carter, J; Hall, J; de Belder, M
Abstract : Introduction: Treatment of patients with out-of-hospital arrest (OOHA) is complex, may be time sensitive and depends on the coordinated actions of diverse healthcare providers. There are no clear guidelines for the management of these patients and there is a lack of outcome data for those presenting with cardiac causes. We reviewed the characteristics and outcomes of a series of patients with OOHA referred and accepted to a tertiary cardiac service. Methods and Result: Between January 2010 and October 2011, 76 pts with OOHA were accepted by our unit. Median age was 62 years (21–91) and 66% were male. The diagnosis of STEMI was made prior to the arrest in 38 pts (Gp 1) and emergency angiography ± PCI was attempted. PCI was done in 36 (95%). 14 (37%) were in cardiogenic shock, 9 (24%) were transferred to ITU, 5 (13.2%) had therapeutic cooling and 33 (87%) survived to hospital discharge. In 20 pts, the diagnosis of STEMI was made following resuscitation (Gp 2). Of these 18 (90%) had angiography + PCI, 9 (45%) were in cardiogenic shock, 6 (30%) had therapeutic cooling, 12 (60%) admitted to ITU, 3 (15%) were admitted to ITU first before coming to the Cath lab and 15 (75%) survived to discharge. There was no evidence of STEMI following resuscitation in 18 pts accepted by our unit (Gp 3). Of these, 17 (94%) had angiography, 7 (39%) had PCI, 2 (18%) had CABG, 2 (18%) were in cardiogenic shock, 15 (83%) were admitted to ITU, 7 (38%) had therapeutic cooling and survival to discharge was 94%. In Gp 3, angiography was delayed pending a head CT in 7 (38%) compared to none in Gps 1 and 2. Angiography was deferred following initial ITU treatment in 8 (44%) patients in Gp 3. Overall survival in patients with and without cardiogenic shock was 58% and 98% respectively (p<0.01). Survival was 87% for those with a witnessed OOHA compared to 40% where the arrest was not witnessed (p<0.05). Conclusion: A programme of immediate cardiovascular assessment of patients with OOHA and referral for angiography and revascularisation as deemed appropriate is associated with encouraging short-term outcomes. Outcomes are related to the presence of shock and whether the OOHA was witnessed or not. National guidance on the immediate management of these patients may improve outcomes.